2009
DOI: 10.1007/s12283-009-0014-7
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the effect of finger–ball friction on the handling performance of rugby balls

Abstract: Handling errors are often seen in professional rugby games and even more so in amateur rugby. This paper analyses the problem of ball mishandling using highspeed video footage of passes and a bespoke finger friction rig. The high-speed video analysis showed that when the ball is caught, often there is a fluctuating movement of the fingers over the surface of the ball. It also showed that the fingers move over the surface of the ball when the ball is thrown, confirming that the dynamic friction is a good measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
40
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(43 citation statements)
references
References 8 publications
2
40
1
Order By: Relevance
“…A finger friction rig, shown in Figure 1, was used to take the friction measurements; a full description of the rig can be found in [18]. The rig uses two load cells to measure both the friction and normal forces.…”
Section: Friction Testsmentioning
confidence: 99%
“…A finger friction rig, shown in Figure 1, was used to take the friction measurements; a full description of the rig can be found in [18]. The rig uses two load cells to measure both the friction and normal forces.…”
Section: Friction Testsmentioning
confidence: 99%
“…Recent tribological studies on materials contacting the skin comprise medical and sports applications [22,23], textiles [24,25] as well as appropriate surfaces for consumer products [20,26,27] and automotive applications [28,29]. The friction and surface properties of materials and objects are known to be essential for their tactile properties.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Sivamani and Maibach [2] tabulated the published values for untreated 'normal' skin that span the range from 0.12 to 3.25. Although previous work has shown that the coefficient of friction depends on a considerable number of factors, such as the body site, the applied normal load, the sliding velocity and the characteristics of the counterbody, the amount of moisture present has a major influence [1][2][3][4][5][6][7][8][9][10]. For example, the coefficient of friction for dry skin typically is reported as having a much smaller value than that in the wet or moist states when sliding against smooth counterbodies [9].…”
Section: Introductionmentioning
confidence: 99%